Accountability and fiscal transfer: The perfect duo for enhancing the regional economy - Bakri, Muhammad Rafi; Putu Permana Bagiada; Yogantari, Ni Luh Rosinta; Marlina, Luh Sri (Jurnal Tata Kelola dan Akuntabilitas Keuangan Negara, 2024)
Each region in Indonesia receives varying amounts of fiscal transfers from the central government, influenced by regional characteristics and accountability. This study examines the impact of fiscal transfers with accountability as a catalyst for the economic growth of Indonesia's regions proxied by gross regional domestic income. The independent variables are the General Allocation Fund (DAU), Special Allocation Fund (DAK), and Revenue Sharing Fund (DBH), while accountability as control variables proxied by BPK audit findings, bureaucratic reform (RB), SAKIP, and APIP scores. Data from 34 provinces over 2016-2020 (170 observations) were analyzed using a fixed effects model and Panel Corrected Standard Error regression. This research fills a gap by examining the simultaneous effects of fiscal transfers on economic growth. The findings indicate that fiscal transfers significantly impact regional economies. The DAK has the highest effect, followed by DBH and DAU. Accountability, measured by APIP, SAKIP, RB scores, and BPK audit findings, is essential for efficient use of transfer funds. BPK audit findings negatively impact the regional economy, underscoring the need for regional governments to improve accountability to optimize central government transfers and support economic growth. Thus, fiscal transfers and accountability are pivotal for enhancing regional financial management and economic performance.